Designing Web APIs with Strapi: Get started with the Strapi headless CMS by building a complete learning management system API - Elshafie, Khalid; Haider, Mozafar (Packt Publishing, 2022)
Leverage the power of Strapi to build self-hosted, customizable, and performant content APIs Key Features Discover how Strapi can help you build APIs quickly and focus on your products and featuresLearn how to put Strapi into practice by implementing it in real-world scenariosUnderstand how to use Strapi's powerful features to customize your APIs Book Description Strapi is a Node.js-based, flexible, open-source headless CMS with an integrated admin panel that anyone can use and helps save API development time. APIs built with Strapi can be consumed using REST or GraphQL from any client. With this book, you'll take a hands-on approach to exploring the capabilities of the Strapi platform and creating a custom API from scratch. This book will help JavaScript developers to put their knowledge to work by guiding them through building powerful backend APIs. You'll see how to effortlessly create content structures that can be customized according to your needs, and gain insights into how to write, edit, and manage your content seamlessly with Strapi. As you progress through the chapters, you'll discover a wide range of Strapi features, as well as understand how to add complex features to the API such as user authentication, data sorting, and pagination. You'll not only learn how to find and use existing plugins from the open-source community but also build your own plugins with custom functionality with the Strapi plugin API and add them to the admin panel. Finally, you'll learn how to deploy the API to Heroku and AWS. By the end of this book, you'll be able to build powerful, scalable, and secure APIs using Strapi. What you will learn Explore Strapi and understand how it worksDefine content types to build APIs quickly and efficientlyUnderstand authentication and authorization in StrapiCreate production-ready APIs with StrapiDeploy the Strapi API to various environments, including Heroku and AWSUse best practices to run the Strapi API in productionSync permissions to access the API between multiple environmentsWrite basic tests for API utilities as well as the endpoint Who this book is for This book is for backend and frontend JavaScript developers. Experienced API developers will learn a new, fast, and flexible way of building APIs, while frontend developers will be able to take a step toward becoming full-stack developers by learning how to leverage Strapi for building APIs quickly. Basic knowledge of JavaScript and REST API concepts is assumed.